Menggali Potensi Kharaj dan Ushr dalam Mendorong Ekonomi Hijau: Perspektif Islam untuk Masa Depan Berkelanjutan - Muharni, Yusraini; Janwari, Yadi; Al Hakim, Sofyan; Rahmah Kusuma, Nurul (Program Studi Ekonomi Syariah Institut Manajemen Koperasi Indonesia, 2025)
The global environmental crisis demands the implementation of sustainable development concepts, including an environmentally friendly green economy. From an Islamic economic perspective, classical fiscal instruments such as kharāj (land tax) and ushr (zakat on agricultural produce) are relevant to supporting the transition to a green economy. This study aims to analyze the potential of kharāj and ushr as green fiscal instruments based on Sharia values. The research method uses a qualitative approach through a literature review of classical (Kitāb al-Kharāj) and modern literature (green economy and sustainable finance). The results of the study indicate that kharāj can be modernized as a green land tax that supports conservation, renewable energy, and reforestation. Meanwhile, ushr can be directed to fund organic agriculture, water management, and the empowerment of smallholder farmers. This study provides a theoretical contribution to the development of an Islamic green fiscal model that is synergistic with the Sustainable Development Goals (SDGs).Keywords: kharaj, ushr, green economy, sustainability, SDGs